2019
DOI: 10.1111/apt.15380
|View full text |Cite
|
Sign up to set email alerts
|

Earlier discontinuation of TNF‐α inhibitor therapy in female patients with inflammatory bowel disease is related to a greater risk of side effects

Abstract: Summary Background In rheumatoid arthritis and psoriasis female sex has been shown to be associated with discontinuation of anti‐tumour necrosis factor‐α (TNF‐α) therapy. Aim To retrospectively assess the association between sex and TNF‐α drug persistence in patients with inflammatory bowel disease (IBD). Methods All IBD patients on anti‐TNF‐α therapy with a minimum follow‐up of 12 months in a single tertiary centre were identified. Patient and treatment characteristics and reasons for anti‐TNF‐α discontinuati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 64 publications
5
27
0
Order By: Relevance
“…A previous study demonstrated that non-adherence to ant-TNF agents is significantly associated with the incidence of LOR to an- ti-TNF agents [14]. A study conducted in the Netherlands revealed that drug persistence for anti-TNF in females was lower than that of males due to a higher rate of side effects in females [15]. The findings of these studies can serve as bases to support our hypothesis.…”
Section: Discussionsupporting
confidence: 74%
“…A previous study demonstrated that non-adherence to ant-TNF agents is significantly associated with the incidence of LOR to an- ti-TNF agents [14]. A study conducted in the Netherlands revealed that drug persistence for anti-TNF in females was lower than that of males due to a higher rate of side effects in females [15]. The findings of these studies can serve as bases to support our hypothesis.…”
Section: Discussionsupporting
confidence: 74%
“… 40 A recent study published in 2019 reported that female sex was associated with a higher risk of discontinuation of anti-TNF therapy in IBD due to higher rates of drug intolerance. 41 In the same study, other factors such as greater age at start of anti-TNF therapy and dose escalation were found to be associated with discontinuation. 41 Similar findings were reported by another study where a greater age of patient was associated with higher risk of discontinuation and treatment failure.…”
Section: Discussionmentioning
confidence: 86%
“… 41 In the same study, other factors such as greater age at start of anti-TNF therapy and dose escalation were found to be associated with discontinuation. 41 Similar findings were reported by another study where a greater age of patient was associated with higher risk of discontinuation and treatment failure. 42 Our cohort identified some new risk factors which predict poor outcomes after discontinuation of biologics which could guide decision making.…”
Section: Discussionmentioning
confidence: 86%
“…Proinflammatory cytokines are known to be mediators during the onset of disease, and they play critical roles in immune status and inflammatory response. Tumor necrosis factor alpha (TNF-a) is one of the major proinflammatory factors relevant to the pathogenesis of IBD (Schultheiss et al, 2019). Popivanova et al (2008) reported that the combined treatment with Azoxymethane and DSS induced the intracolonic expression of TNF-a and blocking of TNF-a reversed carcinoma progression with less inflammatory infiltrate.…”
Section: Discussionmentioning
confidence: 99%